Victim participation in practice at the International Criminal Court: Kenya 2 case study - Dodgson, Kate (2015)
This minor dissertation examines victim participation at the International Criminal Court in practice, focusing on the Kenya 2 proceedings. Victim participation has always been a significant part of the mandate of the International Criminal Court, however, the actual practice of victim participation is not well expounded upon in the Rome Statute or through the legal texts of the Court. It has largely been left up to individual chambers to determine and design what modality of victim participation is suitable for the circumstances of the case before it. The Kenya situation presented a number of novel circumstances that required the Court and Counsel to implement new and innovative victim participation practices. The failures and successes of the Kenya victim participation methods deserve to be documented so that lessons can be learnt for current and future victim participation practices